Genetska diferenciacija avtohtonih populacij smreke (Picea abies (L.) Karst.) v Sloveniji, ugotovljena z analizo izoencimov - Božič, Gregor (Zbornik gozdarstva in lesarstva, 2003)
Genetic differentiation of 22 indigenous Norway spruce (Picea abies (L.) Karst) populations from Slovenia and 4 from Croatia has been investigated by means of isoenzyme gene markers. The degree of differentiation among populations has been measured with genetic distances proposed by Gregorius (1974) for 15 polymorphic gene loci. Multilocus estimates of genetic distancesrange between 0.021 and 0.073 (in Slovenia up to 0.063). Norway spruce populations did not show a strong genetic differentiation by isozymes. The results of hierarchical classification indicated a geographically dependent pooling of populations into two distinct groups: Alpine group including Trnovski gozd and Central Dinaric group, with the two groups overlapping in the Snežnik area.
Keywords: Croatia; genetska diferenciacija; Hrvaška; izoencimi; Picea abies; Slovenia; Slovenija